Pengaruh Rasio Likuiditas, Rasio Profitabilitas Dan Rasio Aktivitas Terhadap Kinerja Keuangan PT. Adaro Energy Tbk - Ramdhani Ramdhani; Aliah Pratiwi (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to examine the influence of liquidity ratios, profitability ratios and activity ratios on the financial performance of PT. Adaro Energy Tbk. This research is a type of associative research. The population used in the research was the financial report of PT Adaro Energy Tbk. For 16 years since it was listed on the Indonesian Stock Exchange (BEI), namely 2005-2021. The sample technique used was purposive sampling, so the sample in this study was 10 years of financial reports. The research results based on the F test show that there is no significant influence simultaneously between Current Ratio, Net Profit Margin, Total Asset Turn Over on financial performance at PT. Adaro Energy Tbk.